An Early Intervention Program to Optimize Articulation Skills in Deaf Children - Carol, Aileen; Aprilia, Imas Diana (Journal of Education for Sustainability and Diversity, 2023)
This study is motivated by the existence of speech barriers in deaf children aged 6 years, indicated by the lack of clarity in pronouncing vocal letters. This condition is allegedly the result of inappropriate intervention services from the family. The purpose of this study is to describe a family-sourced early intervention program for deaf children who experience speech delays, especially in the ability to pronounce vowels. The research method used is descriptive qualitative, with the research subject is 1 family and their children who experience hearing barriers (deaf). The results of this study are the formulation of a hypothetical program consisting of rationale, objectives, materials, strategies, and evaluations that have been validated so that it is feasible to guide families in intervening language and communication development services for their children appropriately.